Oxidative stress markers in initial therapy and remission of nephrotic syndrome and serum malondialdehyde level predictor from routine laboratory test - Riska Habriel Ruslie; Oke Rina Ramayani; Darmadi Darmadi; Gontar Alamsyah Siregar (Medicinski glasnik, 2021)
Aim To compare oxidative stress state of children with nephrotic syndrome at the first week of treatment and in remission, and to predict malondialdehyde (MDA) level from routine laboratory tests. Methods This cross-sectional study involved 80 1-18 years old children with nephrotic syndrome, who were divided into two groups: initial group (40 children in the first week of therapy) and remission group (40 children in remission). Demographic characteristics of the patients were taken by a questionnaire. Laboratory tests were measured in the initial group; in the remission group negative or trace proteinuria was measured for three consecutive days. Serum urea, creatinine, albumin, total cholesterol, MDA, superoxide dismutase, glutathione peroxidase, and urine albumin-to-creatinine ratio (UACR) were measured and compared between the groups. Albumin, total cholesterol, and UACR were subjected to predict high serum MDA using a mean of all patients’ MDA level as a cutoff. Results There were higher albumin levels and lower UACR, total cholesterol, and MDA in the remission group compared to the initial group. Albumin and UACR showed good accuracy, and total cholesterol showed very good accuracy to predict serum MDA level more than 1.35 µmol/L. Conclusion Children with nephrotic syndrome in the first week of therapy showed a higher oxidative stress state than the children in remission. Serum albumin, serum total cholesterol, and UACR can predict serum MDA level with good accuracy.
Keywords: antioxidant; glutathione peroxidase; nephrosis; reactive oxygen species; superoxide dismutase